PROFILE OF ANTIBACTERIAL ACTIVITY OF FRACTIONS FROM METHANOL EXTRACTS OF GARCINIA LATISSIMA MIQ. FRUIT RIND - Ambarwati, Neneng siti Silfi; Malik, Amarila; Elya, Berna; Hanafi, Muhammad (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: A previous study showed that methanol extracts of Garcinia latissima Miq. demonstrated antibacterial activity against Bacillus subtilis, Staphylococcus aureus, and Pseudomonas aeruginosa. The aim of this study was to obtain active antibacterial fractions from methanol extracts of G. latissima Miq. Methods: Fractionation of extracts was performed on G60 silica gel column chromatography using n-hexane eluent, ethyl acetate, and methanol. Antibacterial tests were done using the paper disc method to determine the zone of inhibition, the microdilution method to determine the minimum inhibitory concentration (MIC), and a bioautographic test. Results: Fractions A-E, and F had zones of inhibition against B. subtilis. Fractions A-E had zones of inhibition against S. aureus. Fractions C-E had zones of inhibition against P. aeruginosa. The bio-autograph test showed zones of inhibition on several bio-autographic spots, indicating that active compounds were obtained from the fractionation of methanol extract from G. latissima Miq. fruit rind. Fraction D's MIC against B. subtilis, S. aureus, and P. aeruginosa was 312.5 ppm. The MIC of Fraction C against B. subtilis and of Fraction R against P. aeruginosa also was 312.5 ppm. Conclusion: Fraction D was the most active fraction against the three test bacteria.